2010
DOI: 10.1262/jrd.09-086t
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Real-time Radiotelemetric Pedometer for Estrus Detection and Insemination in Japanese Black Cows

Abstract: Abstract. The objective of this study was to investigate the efficiency of estrus detection and determination of the time of ovulation in Japanese Black cows by a real-time radiotelemetric pedometer. A herd of Japanese Black cows was housed in a loose-housing barn. This pedometer system and a pressure-sensing radiotelemetric device, which detects standing events, were concurrently compared in regard to their availability for detection of estrus events. Pedometer estrus and standing events were observed for all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 15 publications
(30 reference statements)
2
19
0
Order By: Relevance
“…These results showed that the pedometer was an effective device for detecting estrus in Japanese Black cattle in ST heat. This finding agreed with previous reports which measured steps in Japanese Black cattle (Yoshioka et al., ). Furthermore, the number of steps clearly increased during estrus in silent heat as well as in ST heat, suggesting that the radiotelemetric pedometer is useful for detecting estrus in Japanese Black cattle (Figures and ), even in silent heat.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…These results showed that the pedometer was an effective device for detecting estrus in Japanese Black cattle in ST heat. This finding agreed with previous reports which measured steps in Japanese Black cattle (Yoshioka et al., ). Furthermore, the number of steps clearly increased during estrus in silent heat as well as in ST heat, suggesting that the radiotelemetric pedometer is useful for detecting estrus in Japanese Black cattle (Figures and ), even in silent heat.…”
Section: Discussionsupporting
confidence: 94%
“…To calculate the estrus duration, the beginning of estrus (0 hr) was determined when the numbers of steps (/hr) became 1.5‐fold higher than the 14‐day average before estrus (steps/hr) and remained at this higher level for more than 3 hr (Sakatani, Balboula, Yamanaka, & Takahashi, ; Sakatani et al., ; Yoshioka et al., ). The end of estrus was defined as the time when the steps/hr returned to less than 1.5 times the 14‐day average level.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations